Direct Seed Marketing boosts seed availability and improves crop yields and commercialization in Ethiopia (26% increase in maize yield) - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Ethiopia’s Direct Seed Marketing (DSM) innovation, scaled up to 290 woredas and 1.5 million smallholder farmers in 2019, improved seed availability for maize, wheat, and teff and led to significantly positive effects on maize productivity (26% increase in yield) and commercialization (5% increase in the share of harvest sold). PIM research had informed the scaling of DSM and a PIM team conducted an ex-post impact assessment of DSM in 2020.